Structural and Functional Characterization of CreFH1, the Frataxin Homolog from Chlamydomonas reinhardtii - Terenzi, Agustina (2022)
Frataxin plays a key role in cellular iron homeostasis of different organisms. It has been implicated in iron storage, detoxification, delivery for Fe-S cluster assembly and heme biosynthesis. However, its specific role in iron metabolism remains unclear, especially in photosynthetic organisms. To gain insight into the role and properties of frataxin in algae, we identified the gene CreFH1, which codes for the frataxin homolog from Chlamydomonas reinhardtii. We performed the cloning, expression and biochemical characterization of CreFH1. This protein has a predicted mitochondrial transit peptide and a significant structural similarity to other members of the frataxin family. In addition, CreFH1 was able to form a dimer in vitro, and this effect was increased by the addition of Cu2+ and also attenuated the Fenton reaction in the presence of a mixture of Fe2+ and H2O2. Bacterial cells with overexpression of CreFH1 showed increased growth in the presence of different metals, such as Fe, Cu, Zn and Ni and H2O2. Thus, results indicated that CreFH1 is a functional protein that shows some distinctive features compared to its more well-known counterparts, and would play an important role in response to oxidative stress in C. reinhardtii.